Alcance de la debida diligencia para identificar el lavado de activos en la cooperativa de ahorro y crédito ERCO Ltda. - Aucapiña Maza, Johana Beatriz (2025)
The objective of this research was to determine the Scope of the Due Diligence to be applied by the Credit and Savings Cooperative Erco Ltda. in order to identify money laundering as stipulated in Resolution NRO. SEPS-IGT-IGS-INSESF-INR-INGINTINSEPS-IGJ-0121. Documentary analysis and interviews with specialists have confirmed that globalisation and technological advances present new risks, making it indispensable for companies to implement robust due diligence policies. These policies should include customer identification and verification, continuous monitoring of transactions and updating of information, especially in cases of politically exposed persons and non-tax resident accounts. Erco Ltd. adheres to these procedures to ensure the integrity and legality of its operations through a rigorous and well-founded application of due diligence by identifying politically exposed persons, maintaining updated files (folders), verifying checklists, collecting member identification forms, constant monitoring of transactions with high denomination banknotes, identification of active non-resident accounts, thus contributing to the strengthening of trust in the cooperative sector.